Emozioni e politica: Per un confronto tra individualismo e valori collettivi - Iapoce, Angiola (B@belonline, 2022)
Some notes about the relationship between personal and private emotions and the construction of a society really democratic, respectful of the individual feelings. It’s necessary a path for a renewed subject, without a split between private life and public face. We need the great psychoanalytical lesson on the value of emotions and feelings. It’s necessary to respect the concrete worth of the single human being against every abstract way of social life.